Construction of an FeNi-Mo2C@SiO2 monolith electrocatalyst with an increased number of active sites and enhanced intrinsic activity toward water oxidation. (8th February 2023) - Chen, Huanyu; Bai, Jia-Qi; Wei, Yuxue; Chen, Jingshuai; Sun, Song; Mao, Chang-Jie
Abstract : A novel FeNi-Mo2 C@SiO2 monolith electrocatalyst was constructed to boost the OER due to the increased number of active sites and enhanced intrinsic activity. Abstract : The exploration of high-efficiency and Earth-abundant electrocatalysts for the oxygen evolution reaction (OER) remains a tremendous challenge. Herein, an ultrafine FeNi–Mo2 C composite immobilized on the surface of SiO2 support is fabricated through annealing a mixture of Fe, Ni and Mo precursors and SiO2 nanospheres. The electronic structure of the FeNi alloy is tuned by combining with Mo2 C, forming a hybrid architecture with enhanced intrinsic activity of active sites. The introduced SiO2 nanospheres reduce the nanoparticle size of the FeNi–Mo2 C composite, further increasing the population of the surface electrochemically active sites. Benefiting from the compositional and structural merits, the FeNi-Mo2 C@SiO2 electrocatalyst exhibits excellent OER behavior with a small overpotential of 180 mV to reach a current density of 10 mA cm −2, an ultra-small Tafel slope of 11.0 mV dec −1, and good stability in alkaline media. The outstanding OER performance is attributed to the increased number and enhanced intrinsic activity of active sites due to the synergistic effect of each component. This study provides a promising way to design and develop an advanced electrocatalyst towards water oxidation.